2021
DOI: 10.21203/rs.3.rs-809686/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Central Corneal Thickness in Adults With Indications For Kidney Transplantation and Commenting On Some Related Factors

Abstract: Objectives Central corneal thickness (CCT) is an important biological indicator of eyeball affecting intraocular pressure, which plays a vital role in glaucoma pathology. This study investigated the central corneal thickness in renal failure subjects with indications for kidney transplantation and commented on some related factors. Methods A cross-sectional descriptive study was conducted from January to June 2021 in Hanoi, Vietnam. Ninety-six adult patients with grade 3 and 4 renal failure indicated kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Significantly, the OSDI score gradually increased, and the Schirmer value gradually decreased from the group of hypertensive patients stage I to III, P<0.001 (Table 2). We found that there were some factors related to this result because age, plasma creatinine, and CRP-hs levels increased gradually from the group of patients with stage I to stage III hypertension, P<0.001 (Table 2), that the factors have all been confirmed by previous studies to be related to DEs [20][21][22][23] . In multivariate analysis, we found that advanced age, long duration of hypertension, diabetes mellitus, elevated plasma creatinine, and CRP-hs are independent factors associated with DE in patients with primary hypertension, P<0.01 (Table 4).…”
Section: Relation Dry Eye and Disease Stage Some Factors In Primary H...supporting
confidence: 74%
“…Significantly, the OSDI score gradually increased, and the Schirmer value gradually decreased from the group of hypertensive patients stage I to III, P<0.001 (Table 2). We found that there were some factors related to this result because age, plasma creatinine, and CRP-hs levels increased gradually from the group of patients with stage I to stage III hypertension, P<0.001 (Table 2), that the factors have all been confirmed by previous studies to be related to DEs [20][21][22][23] . In multivariate analysis, we found that advanced age, long duration of hypertension, diabetes mellitus, elevated plasma creatinine, and CRP-hs are independent factors associated with DE in patients with primary hypertension, P<0.01 (Table 4).…”
Section: Relation Dry Eye and Disease Stage Some Factors In Primary H...supporting
confidence: 74%